The state residential community Topol-1 on the slope of the vstrechnaia balka in march 2011 - Бабич, Филипп Владимирович; Седин, Владимир Леонидович; Ковалëв Вячеслав Викторович (Eastern-European Journal of Enterprise Technologies, 2012)
On the basis of personal annual supervision, the analysis of designing decisions and studying of stages of building of a slope since 1970 of the Vstrechnaia beam by a many-storeyed inhabited file of Topol-1 in Dnepropetrovsk sity, understands the history of the emergence and development of landslide processes